Sustainability Efforts Analysis on Influencing Purchase Decisions of Fast Fashion Brands - Nasution, Dalilah Saila Jumara Dani; Hanoum, Syarifa; Agustin, Harisatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2024)
In recent years, the fashion sector has had a significant envi-ronmental impact, particularly due to its considerable contri-bution to greenhouse gas emissions and waste. Recognizing the growing population of eco-conscious consumers alongside the persistent shift towards digital platforms, fashion brands, par-ticularly those in the fast fashion segment, are increasingly prioritizing sustainability efforts and strategically communi-cating them to their target audience. Against this backdrop, this study, situated in the context of Indonesia, aims to exam-ine the perceptions of fast fashion consumers regarding brands’ sustainability efforts. Through an extensive review and analysis of relevant literature, this research explores the multifaceted dynamics through which sustainability efforts influence consumer perceptions and subsequently shape pur-chase decisions in the fast fashion realm. The methodology employed in this study centers around Partial Least Square-Structural Equation Modelling (PLS-SEM), a robust analyti-cal framework suited for exploring complex relationships and latent constructs. The findings of this investigation underscore the pivotal role of sustainability efforts in shaping consumer perceptions and purchase intentions within the fast fashion domain. By shedding light on the underlying mechanisms driv-ing consumer behavior in the context of fast fashion sustaina-bility, this research contributes valuable insights to both aca-demia and industry practitioners, facilitating a deeper under-standing of the evolving dynamics within the fashion sector and informing strategic decision-making processes aimed at fostering sustainable consumption patterns and promoting responsible business practices.